2003
DOI: 10.1002/nau.10078
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical electrical stimulation in the treatment of micturition dysfunction in children

Abstract: It is concluded that IVES is a promising method to treat the underactive detrusor in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 26 publications
2
44
0
Order By: Relevance
“…Other reports of end-organ stimulation exist [12]. A recent study has cited the benefit of stimulation of the bladder wall with electrodes on the end of a urethral catheter in the bladder in children [13]. Urinary retention in these individuals was due to a variety of disorders, and periodic stimulation resulted in improved micturition.…”
Section: Introductionmentioning
confidence: 99%
“…Other reports of end-organ stimulation exist [12]. A recent study has cited the benefit of stimulation of the bladder wall with electrodes on the end of a urethral catheter in the bladder in children [13]. Urinary retention in these individuals was due to a variety of disorders, and periodic stimulation resulted in improved micturition.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In an earlier study we showed that a sawtooth waveform was equally effective as a square wave for inducing a detrusor contraction if the average input charge was the same. The study also revealed that the average power could be reduced without decreasing the efficacy of the stimulation by changing the frequency or pulse duration.…”
Section: Discussionmentioning
confidence: 97%
“…[1][2][3][4][5] However, the technique has not found wide clinical acceptance because the treatment success rate is not consistent and the results are difficult to reproduce. 1,6 This might be due to patient selectio n, but very likely the influence of methodological issues such as type of stimulation parameters will be important too.…”
Section: Introductionmentioning
confidence: 98%
“…There is evidence that electrotherapy in adults has the potential to improve detrusor contractility and facilitate complete bladder emptying [Thon et al, 1991;Jonas et al, 2001;Primus et al, 2001]. Gladh et al [2002] investigated the e¡ect of intravesical electrical stimulation on the emptying ability of children with both neurogenic and idiopathic detrusor underactivity and noted that voiding was normalized following treatment in 85% of children.The e¡ect was long lasting in 72%; gains being more marked in children with idiopathic rather than neurogenic detrusor dysfunction. Other studies suggest that electrical therapy in children with neurogenic bladder dysfunction is associated with improved bladder storage and enhanced emptying, but may only generate a minimal improvement in continence.…”
Section: Paediatric Applicationmentioning
confidence: 99%